PENYULUHAN EKONOMI KOPERASI BAGI GENERASI MILENIAL - Wahyudi, Heru; Nairobi; Suparta, I wayan; Palupi, Widia Anggi (Faculty of Economics and Business Lampung University, 2023)
Cooperatives are one of the Soko guru of the national economy. If this soko guru is good, it will suit the country’s economic system and vice versa. If the soko guru is damaged, it will affect the whole national economic order. The cooperative economy prioritizes mutual aid for the welfare of members and the wider community. Knowledge about the economy based on local potential and the pattern of the national economy, namely the cooperative economy, must begin to be grounded to the millennial generation who will continue the struggle. Noting these problems, the Faculty of Economics, through the implementation team of Heru Wahyudi, felt called to carry out a community service activity by collaborating with LP2M Lampung University and managing the At-Tarbiyah Mosque. The action in question was entitled Cooperative Economic Counseling for Millennial Generation which took place on Thursday, October 3, 2019, with a total of 30 participants—presentation of material by speakers in the form of lectures, discussions, questions, and answers. The material presented included an introduction to the economic basis of cooperatives, member participation, and cooperative formation procedures, as well as the characteristics of Indonesian cooperatives, which were successfully absorbed well by 90% of participants with A grades and the rest with B grades.